2D Star‐Shaped Non‐Fullerene Electron Acceptors with Modulation of J‐/H‐Type Aggregations: Molecular Design–Morphology–Electrical Property Correlation. Issue 6 (4th May 2020) - Koh, Chang Woo; Cho, Hye Won; Rashid, Md Al Mamunur; Lee, Tack Ho; Park, Song Yi; Lee, Wonho; Kwak, Kyungwon; Kim, Jin Young; Woo, Han Young
Abstract: Two kinds of A1 ‐(D‐A2 )3 ‐type (A1, A2 : acceptor, D: donor) triazine‐based star‐shaped acceptors, TzTPT‐INCN and TzCDT‐INCN, are reported to show strong face‐on orientation with J‐ to H‐type packing structural transformation with thermal annealing (TA) treatments. TA of the thin films of both acceptors mainly leads to the formation of thermodynamically more stable H‐type packing with enhanced hypsochromic absorption peaks in the UV–vis spectra. The results agree well with calculations based on time‐dependent density‐functional theory. To determine the optimum TA conditions for fabricating organic photovoltaic (OPV) devices, in‐depth studies are conducted through in situ grazing incidence wide‐angle X‐ray scattering to analyze changes in the molecular packing structure with respect to the TA temperature employed. Sequential deposition bilayer OPV devices are fabricated by combining the two acceptors with a donor polymer PBDB‐T. Although the electron mobilities and power conversion efficiencies are improved slightly (PBDB‐T/TzTPT‐INCN: 4.26 to 4.65%, PBDB‐T/TzCDT‐INCN: 6.58 to 7.18%) via transformation from a J‐dominant to H‐dominant morphology, the differences are not significant. Similar charge transport characteristics are observed for both the H‐ and J‐type stacked structures. The study can be used to better understand the modification of molecular packing via the manipulation of molecular design and to determine the correlation between packing structures and electrical properties. Abstract : Two structurally related triazine‐based star‐shaped acceptors are synthesized and they have strong face‐on orientation with J‐ to H‐type packing structural transformation with thermal annealing treatments. The correlations of molecular design, J‐/H‐type packing structures, and the corresponding electrical properties are studied in detail.